Conducting research interviews for business and management students - Cassell, Catherine (London : SAGE Publications Ltd, 2015)
Part of SAGE's new Mastering Business Research Methods series, conceived and edited by Bill Lee, Mark N. K. Saunders and Vadake K. Narayanan. The series is designed to support business and management students with their research-based dissertations by providing in-depth and practical guidance on using a chosen method of data collection or analysis. The books are written in a concise and accessible way, and contain a range of features, including checklists and a glossary, designed to support self-guided research. In Conducting Research Interviews, Catherine Cassell guides you through conceptualizing the interview, preparing for the research interview, conducting the interview, examples, and conclusions and next steps. View the complete list of new and forthcoming Mastering Business Research Methods series.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business -- Research -- Methodology; Management -- Research -- Methodology; Interviewing; Qualitative research